Assessing the Global Economic and Poverty Effects of Antimicrobial Resistance - Ahmed, Syud Amer (World Bank, Washington, DC, 2017)
This paper assesses the potential impact of antimicrobial resistance on global economic growth and poverty. The analysis uses a global computable general equilibrium model and a microsimulation framework that together capture impact channels related to health, mortality, labor productivity, health care financing, and production in the livestock and other sectors. The effects spread across countries via trade flows that may be affected by new trade restrictions. Relative to a world without antimicrobial resistance, the losses during 2015–50 may sum to $85 trillion in gross domestic product and $23 trillion in global trade (in present value). By 2050, the cost in global gross domestic product could range from 1.1 percent (low case) to 3.8 percent (high case). Antimicrobial resistance is expected to make it more difficult to eliminate extreme poverty. Under the high antimicrobial resistance scenario, by 2030, an additional 24.1 million people would be extremely poor, of whom 18.7 million live in low-income countries. In general, developing countries will be hurt the most, especially those with the lowest incomes.